Auditor Attributes and Audit Quality in Emerging vs Developed Economies: A Comparative Systematic Literature Review - Wafiq Azizah Reski Amaliah; Muh. Silmi Kaffah Yusuf; Amiruddin Amiruddin; Syamsuddin Syamsuddin (Transpublika Publisher, 2025)
Audit quality underpins financial transparency and accountability and is shaped by auditor attributes such as integrity, competence, independence, experience, and affiliation with major firms. This study aims to compare the influence of these attributes on audit quality in emerging versus developed economies. Employing a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol, we analyzed 35 peer‑reviewed articles published between 2010 and 2025. Our findings indicate that, in developed economies, robust regulatory frameworks, mature corporate‑governance mechanisms, and stringent oversight facilitate the effective deployment of auditor attributes, resulting in higher audit quality. In contrast, emerging economies face structural challenges such as weak enforcement, political interference, and resource limitations that diminish the impact of these attributes. Across both contexts, independence and competence consistently enhance audit quality, whereas the effects of experience and firm affiliation depend on the strength of the institutional environment. These insights underscore the need for global context‑specific, adaptive strategies to strengthen audit quality. Regulators and stakeholders are encouraged to tailor policies and support mechanisms to address institutional gaps and bolster auditors' capacity to uphold rigorous standards.